2008
DOI: 10.1111/j.1600-9657.2007.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple crown‐root fractures in primary molars and a suspected subcondylar fracture following trauma: a report of a case

Abstract: Dental trauma is common and often more than one injury is found. Injuries to the primary dentition are usually luxations and mandibular fractures rarely occur. With trauma sustained to the chin, the posterior primary teeth are at increased risk of trauma and mandibular fractures can occur. The case discussed is of a 4-year-old female who presented 2 weeks following dental trauma with multiple primary molar fractures and a possible subcondylar fracture. The need for a detailed examination is emphasized and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Treatment may also depend on the ability of the child to cooperate with the treatment and number of teeth involved. There have been reports of fractured primary molars where extraction was treatment of choice followed by space maintainer,10 19 20 whereas in the present case only crown fracture was diagnosed, which was successfully treated by carrying out pulp therapy and full crown restorations.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Treatment may also depend on the ability of the child to cooperate with the treatment and number of teeth involved. There have been reports of fractured primary molars where extraction was treatment of choice followed by space maintainer,10 19 20 whereas in the present case only crown fracture was diagnosed, which was successfully treated by carrying out pulp therapy and full crown restorations.…”
Section: Discussionmentioning
confidence: 56%
“…Crown root fractures in primary molars are extremely rare and usually occur as a result of trauma to the chin 10. However, fractures of the posterior primary teeth are also often overlooked as in this case where the fractured teeth were not detected in accidental fall and emergency at the time of injury and there was a subsequent 3 weeks delay.…”
Section: Discussionmentioning
confidence: 84%
“…In this cases series, the majority of injured teeth were indeed incisors (95.7%), and only one case affected a molar. Crown-root fractures in the primary molars are the most rare type of such injuries, and these generally result as a consequence of indirect trauma (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…It has been emphasized the harmful effects on space problems such as tipping of the first permanent molar, crowding of the dental arch, and impaction of the permanent sucessor 18) . Multiple, vertical, complicated fractures in primary molars are uncommon, and only a few cases have been reported worldwide over the past 40 years 11,13,[19][20][21] . In this respect, Needleman and Wolfman 11) reported the case of a 5-year-old who presented crown-root fractures in the primary mandibular second molars; both teeth were extracted and distal-shoe space maintainers were placed.…”
Section: Discussionmentioning
confidence: 99%
“…Sasaki et al 21) presented 2 cases, aged 4 and 7, with multiple crown-root fractures due to injuries to the chin; in the 2 patients the treatment was conservative, with pulp treatment and stainless steel crowns. Tejani et al 13) reported on a 4-year-old female who presented 2 weeks following a chin blow, with multiple primary molar fractures requiring extractions, which were carried out under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%